IMPROVING LESSON EFFECTIVENESS THROUGH DIGITAL TECHNOLOGIES - Jonibekov Doniyor Baxtiyor o‘g‘li (The Conference Hub, 2025)
This article thoroughly examines the application of digital technologies in the educational process and their role in increasing lesson effectiveness. It explores how digital tools can improve the quality of education, enhance student engagement, and enable teachers to work more efficiently. The paper outlines the advantages of digital technologies, the need to develop digital competencies among teachers and students, and presents successful practical experiences. It also provides recommendations for the future development of digital education and outlines necessary steps for improvement.
Keywords: Digital technologies, education effectiveness, lesson quality, digital competencies, teachers, students, e-learning, online platforms, interactive learning, digital literacy, artificial intelligence, virtual reality, distance learning.